Breeding system in a population of the globose cactus Mammillaria magnimamma at Valle del Mezquital, Mexico - Callejas-Chavero, Alicia; Vargas-Mendoza, Carlos F.; Gomez-Hinostrosa, Carlos; Arriola-Padilla, Victor J.; Cornejo-Romero, Amelia (Botanical sciences, 2021)
Background: The breeding system of Mammillaria magnimamma was initially described as hermaphroditic. However, some individuals in a natural population at Valle del Mezquital exhibited a seemingly non-functional androecium. Objectives: To determine the breeding system of M. magnimamma through morphological characterization of floral types. Study site and years: The study was conducted at Valle del Mezquital, Mexico, during the 2019 reproductive season. Methods: We characterized floral polymorphism by means of scanning electron microscopy and morphometric analysis of 18 floral traits. Pollinator frequency, size and number of seeds, and germination rate were compared between flower types. Results: 87.85 % of the plants were hermaphrodites, and 12.15 % were females with non-functional androecium, with significantly smaller stamens, indehiscent anthers, and malformed pollen. Female flowers were shorter (14.007 ± 0.742 mm) and had smaller (1.856 ± 0.151 mm) nectar chambers than hermaphroditic flowers (15.821 ± 0.450 and 2.194 ± 0.090 mm, respectively). Although pollinators visited hermaphrodites (124 visits) about twice as often as pistillate flowers (60 visits), the latter produced more numerous ( F 1,26 = 8.320, P = 0.003) and larger  ( Hc = 4.637, P = 0.031) seeds that also germinated faster ( Hc = 70.59, P < 0.0001). Conclusions: This M. magnimamma population exhibits a gynodioecious breeding system with both hermaphroditic and male sterile female plants. Females produce more, higher quality seeds, which favour their maintenance in the population.